Comparison of the prognostic value of stress and rest pulmonary transit time estimation using myocardial perfusion CMR. (13th July 2021) - Seraphim, A; Knott, K; Menacho, K; Augusto, J; Davies, R; Joy, G; Hui, X; Treibel, T; Cooper, J; Petersen, S; Fontana, M; Hughes, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Clinical Research Training Fellowship Background: Pulmonary transit time (PTT) is a quantitative biomarker of cardiopulmonary status. Rest PTT was previously shown to predict outcomes in specific disease models, but clinical adoption is hindered but challenges in data acquisition. Whether evaluation of PTT during stress encodes incremental prognostic information has not been previously investigated as scale. Objectives: To compare the prognostic value of stress and rest PTT derived from a fully automated, in-line method of estimation using perfusion CMR, in a large patient cohort. Methods: A retrospective two-center study of patients referred clinically for adenosine stress myocardial perfusion assessment using CMR. Analysis of right and left ventricular cavity arterial input function curves from first pass perfusion was performed automatically, allowing the in-line estimation of both rest and stress PTT. Association with major adverse cardiovascular events (MACE) was evaluated. MACE was defined as a composite outcome of myocardial infarction, stroke, heart failure admission and ventricular tachycardia or appropriate ICD treatment (including ICD shock and/or anti-tachycardia pacing). Results: 985 patients (67% male, median age 62 years (IQR 52, 71)) were included, with median left ventricular ejection fraction (LVEF) of 62% (IQR 54-69). Median stress PTT was shorter than rest PTT 6.2 (IQR 5.1, 7.7) seconds versus 7.7 (IQR, 6.4, 9.2) seconds. Stress and rest PTT were highly correlated (r = 0.69; p < 0.001). Stress PTT also correlated with LVEF (r=-0.37), stress MBF (r=-0.31), LVEDVi (r = 0.24), LA area index (r = 0.32) (p < 0.001 for all). Over a median follow-up period of 28.6 (IQR, 22.6 35, 7) months, MACE occurred in 61 (6.2%) patients. After adjusting for prognostic factors, both rest and stress PTT, independently predicted MACE, but not all-cause mortality. For every 1xSD (2.39s) increase in rest PTT the adjusted hazard ratio (HR) for MACE was 1.43 (95% CI 1.10-1.85, p = 0.007). The hazard ratio for one standard deviation (2.64s) increase in stress PTT was 1.34 (95% CI 1.048-1.723; p = 0.020) after adjusting for age, LVEF, hypertension, diabetes, sex and presence of LGE Conclusions: In this 2-center study of 985 patients, we deploy a fully automated method of PTT estimation using perfusion mapping with CMR and show that both stress and rest PTT are independently associated with adverse cardiovascular outcomes. In this patient cohort, there is no clear incremental prognostic value of stress PTT, over its evaluation during rest. Figure 1. Stress and Rest Pulmonary Transit Time estimation using myocardial perfusion CMR Figure 2. Event-free survival curves for major adverse cardiovascular events (Heart failure hospitalization, myocardial infarction, stroke and ventricular tachycardia/ICD treatment) according to mean rest PTT (8.05seconds) and mean stress PTT (6.7seconds). Log-rank for both p < 0.05